Framework of land use planning for an energy producing city of Northwest China based on water-energy-food nexus - Fang, Zhou; Xue, Shi; Cheng, Changgao; Zhou, Qin; Ali, Maroof; Xu, Rui; Xu, Jinxue; Ding, Tonghui; Wang, Jie; Huang, Zhongde; Sun, Xiping; Bai, Yang (Journal of cleaner production, 2024)
The development of cities and their industries is constrained by the water-energy-food nexus (WEF nexus) formed under certain biophysical conditions. Urban-scale WEF nexus research is very different from macroscale (global or national) research. There is a need for quantitative optimization of several economic sectors, as well as spatial heterogeneity of resource endowments, to develop policies that are distinctive for different levels of endowments. Currently, China is implementing Territorial Spatial Planning (TSP) at all administrative levels throughout the country. Its theoretical basis is to realize the overall management of urban ecological protection land, urban expansion, and industrial growth by measuring the resource carrying capacity and land development suitability of each plot. This provides an opportunity to explore the interconnections between WEF nexus at urban scale by examining the wide range of urban resource availability. Here, we propose the WEF-TSP framework, which helps to realize the multi-objective development needs of regional ecological protection, urban expansion, agricultural development, and energy production in a certain city and provides a decision-making basis for future urban land spatial planning. Ordos, a city in China recognized for its significant energy reserves, has been selected as the subject of a case study. Combined with the spatial heterogeneity of Ordos's resource endowment and focusing on the strong constraints of water resources and ecological protection, this study explores the urban land spatial layout scheme of Ordos in 2030 under different energy development scenarios. It can also provide a reference for other cities in China and even the world to study the spatial layout of urban land use and industrial development based on the WEF nexus.